Frequency of DÉJÀ VU Experience and Its Relationship with Stress in Students of The Medical University of Islamabad - Riaz, Mehwish; Hamza , Hafiz Muhammad; Nayab, Khawaja Uzair; Janjua, Faizan Tanveer; Ali Ashraf, Danish; Malik, Muhammad Muiz (Journal of Rawalpindi Medical College, 2024)
Objective: This research aims to evaluate the frequency of déjà vu experience in medical students and its relationship with stress along with different prognostic factors that lead to déjà vu experience. Methods: A descriptive cross-sectional study was conducted at Foundation University Islamabad over 4 months from May 2023 to August 2023. The sample size (239) was calculated using open Epi software with a previous prevalence of 67%. Stratified random sampling was used to select students. Data was collected through a questionnaire containing demographic variables from a validated déjà vu inventory and stress tool. Analysis was done on a validated déjà vu inventory and perceived stress scale 10. SPSS 26 was used to assess the relationship between stress and the frequency of déjà vu using the chi-square test, with statistical significance at p<0.05. Results: 89.2% of the participants reported that they had experienced this sensation at least once in their life. The most popular ways this feeling happened were in a certain place or a certain situation. The association between stress and Déjà vu experiences was found to be significant(p-value 0.012) Conclusion: 89.2% of the participants reported that they had experienced Déjà vu sensation at least once. There was a significant association between stress among medical university students and Déjà vu experience. Keywords: Déjà vu, Stress, Familiarity, Sensation, Epilepsy, Dopamine.